Volumetric Assessment of Swallowing Muscles: A Comparison of CT and MRI Segmentation - Sporns, Kim Barbara; Hanning, Uta; Schmidt, Rene; Muhle, Paul; Wirth, Rainer; Zimmer, Sebastian; Dziewas, Rainer; Suntrup-Krueger, Sonja; Sporns, Peter Bernhard; Heindel, Walter; Schwindt, Wolfram (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Recent retrospective studies have proposed a high correlation between atrophy of swallowing muscles, age, severity of dysphagia and aspiration status based on computed tomography (CT). However, ionizing radiation poses an ethical barrier to research in prospective non-patient populations. Hence, there is a need to prove the efficacy of techniques that rely on noninvasive methods and produce high-resolution soft tissue images such as magnetic resonance imaging (MRI). The objective of this study was therefore to compare the segmentation results of swallowing muscles using CT and MRI.Methods Retrospective study of 21 patients (median age: 46.6; gender: 11 female) who underwent CT and MRI of the head and neck region within a time frame of less than 50 days because of suspected head and neck cancer using contrast agent. CT and MR images were segmented by two blinded readers using Medical Imaging Toolkit (MITK) and both modalities were tested (with the equivalence test) regarding the segmented muscle volumes. Adjustment for multiple testing was performed using the Bonferroni test and the potential time effect of the muscle volumes and the time interval between the modalities was assessed by a spearman correlation. The study was approved by the local ethics committee.Results The median volumes for each muscle belly of the digastric muscle derived from CT were 3051 mm3 (left) and 2969 mm3 (right), and from MRI they were 3218 mm3 (left) and 3027 mm3 (right). The median volume of the geniohyoid muscle was 6580 mm3 on CT and 6648 mm3 on MRI. The interrater reliability was high for all segmented muscles. The mean time interval between the CT and MRI examinations was 34 days (IQR 25; 41). The muscle differences of each muscle between the two modalities did not reveal significant correlation to the time interval between the examinations (digastric left r = 0.003 and digastric right r = –0.008; geniohyoid muscle r = 0.075).Conclusion CT-based segmentation and MRI-based segmentation of the digastric and geniohyoid muscle are equally feasible. The potential advantage of MRI for prospective studies is the absence of ionizing radiation.Key Points Citation Format
Keywords: computed tomography; magnetic resonance imaging; segmentation; muscle atrophy; sarcopenia; swallowing muscles